Feasibility and acceptability of two remote physical activity programs for older Latino adults: the C.E.R.E.B.R.O. study, a pilot randomized trial - Jocelyn Ocampo-Mota; Yuliana Soto; Miguel A. Negrete; Eduardo Cardiel; Brynne Karlinsey Skidmore; Mariana Pinto; David X. Marquez (Frontiers in Medicine, 2026)
Introduction Expanding access to culturally relevant physical activity (PA) programs is key to supporting healthy brain aging among older Latinos. The C.E.R.E.B.R.O. study compared two Spanish-language PA programs delivered remotely to Latinos with subjective cognitive impairment. BAILAMOS™ was a 6-month Latin dance-based intervention, and ¡En Forma y Fuerte! (Fit & Strong!) was a 3-month multicomponent program. Methods This pilot randomized trial took place remotely via Zoom. Participants were healthy, inactive, and Spanish speaking (aged 60-82). Participants were randomized via computer-generated block randomization to either BAILAMOS™ or ¡En Forma y Fuerte!. The objective of the trial was to compare feasibility of both remote interventions. Feasibility was assessed via (1) reach, (2) recruitment rate, (3) adherence to intervention, (4) retention, and (5) adverse events. Acceptability was assessed quantitatively and qualitatively via a post-program evaluation survey of program components. Results The C.E.R.E.B.R.O. study reached 401 individuals, screened 199 individuals, and enrolled & randomized 38 participants (mean age = 68.89 ± 9.74 years; 75% female). The recruitment rate was 9.48%. Nineteen participants were randomized to BAILAMOS™ and nineteen to ¡En Forma y Fuerte!. Mean attendance for BAILAMOS™ was 55.51% across 48 sessions, while mean attendance for ¡En Forma y Fuerte! was 68.42% across 24 sessions, falling under our pre-determined benchmarks. Retention rates were 84.21% for BAILAMOS™ and 89.47% for ¡En Forma y Fuerte!, meeting our success criteria. Program evaluations highlighted high satisfaction, with higher instructor ratings within ¡En Forma y Fuerte!. No serious adverse events were reported. Discussion Both remotely delivered, culturally tailored PA programs demonstrated strong retention, high participant satisfaction, and acceptable safety among older Latino adults with subjective cognitive impairment. Although recruitment and adherence remained challenging, higher attendance in the shorter-duration program suggests intervention length may influence sustained engagement. These findings support the potential of remote PA programs to increase access among older Latino adults and highlight the need for improved recruitment and engagement strategies in future trials. Clinical Trial Registration https://clinicaltrials.gov/study/NCT05588778?term=NCT05588778&rank=1 , identifier [NCT05588778].